2024
DOI: 10.1002/mco2.544
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of stereotactic body radiotherapy combined with systematic therapy for metastatic renal cell carcinoma: a systematic review and meta‐analysis

Shiyu Zhang,
Xingyu Xiong,
Nan Xie
et al.

Abstract: There is considerable interest in the potential of stereotactic body radiation therapy (SBRT) combined with systemic therapy such as tyrosine kinase inhibitors (TKIs) or immune checkpoint inhibitors (ICIs). However, its efficacy and safety remain unclear. The purpose of this study was to evaluate the efficacy and safety of conducting SBRT during ICI or TKI treatment in different disease settings for patients with metastatic renal cell carcinoma (mRCC). A total of 16 studies were ultimately included. Under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Recent studies have further demonstrated the feasibility of using SBRT in combination with TKIs or ICIs in patients with mRCC, especially those with low metastatic tumor burden. 283 …”
Section: Treatment In Renal Cancermentioning
confidence: 99%
“…Recent studies have further demonstrated the feasibility of using SBRT in combination with TKIs or ICIs in patients with mRCC, especially those with low metastatic tumor burden. 283 …”
Section: Treatment In Renal Cancermentioning
confidence: 99%